RECONSTRUCTIVE SURGERY COMPLICATIONS IN HEAD AND NECK CANCER PATIENTS - D. E. Kulbakin; E. L. Choynzonov; M. R. Mukhamedov; L. A. Kononova; N. M. Khavkin; V. A. Alekseev; E. N. Menkova (Сибирский онкологический журнал, 2021)
The main goal of reconstructive surgery is to improve the quality of life of patients who have undergone surgery. However, recurrences and postoperative complications after such surgeries pose a serious challenge.The purpose of the study was to evaluate immediate surgical outcomes in head and neck cancer patients who underwent reconstructive surgery following tumor resection, as well as to analyze the causes of postoperative complications.Material and Methods. Immediate treatment outcomes were analyzed in 272 head and neck cancer patients, who were treated from 2008 to 2018. All patients were divided into 2 groups. Group I consisted of 172 patients, who underwent radical surgery and reconstruction. Group II comprised 100 patients, who underwent radical surgery alone. The groups were matched by stage, gender, age, previous treatment, and tumor location.Results. The incidence of recurrence was lower in Group I than in Group II (19 % versus 32 %, p>0,05). Postoperative complications occurred in 14 % of patients who underwent reconstruction of postoperative defects with rotation flaps and in 35 % of patients who underwent reconstruction with free revascularized flaps (p<0,05). The rate of complications was higher in patients undergoing maxillary and mandibular reconstructions (39,6 %) than in patients undergoing reconstructions of the other parts of the head and neck (23,7 %) (p<0,05). Patients who received chemoradiotherapy had higher rate of postoperative complications than those who had no neoadjuvant treatment (37 % versus 22 %, p>0,05).Conclusion. Knowledge of the factors that have a significant impact on the likelihood of developing postoperative complications after reconstructive surgeries makes it possible to take measures to prevent  them.